Transition and Motion Sensing System with Nintendo Wiimote and Infra-Red LEDs Array - Raman M.N.A.; Chin Hock G.; Roslan N.; Hamidah Hamid A.S.; Ferdous N. (Institute of Physics Publishing, 2023)
Energy conservation; Environmental technology; Graphical user interfaces; Personal communication systems; Personal computers; Bluetooth wireless communication; Mathematical algorithms; Mathematical formulas; Motion sensing; Nintendo; Presentation slides; Light emitting diodes